PENGARUH AUDIT TENURE PADA ASIMETRI INFORMASI DENGAN KOMPETENSI KOMITE AUDIT SEBAGAI PEMODERASI - Gustiriani Dachlan, Nanda Noor; Widhiyani, Luh Sari (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
This study amis to determine the effect of audit tenure on the asymmetry of information, and the competence of the audit committee can ifluence the relationships audit tenure on information asymmetry. Manufacturing companies listed in Indonesia Stock Exchange in periode 2012-2014 have been selected as the population in this study. Selection sampel in this study using a non-probality sampling and purposive sampling with staples obtained at least 138 companies. Regression analysis techniques moderation is an analytical technique in this study. The analysis shows that the audit tenure negative effect on information asymmetry means that the longer the tenure, the asymmetry of information audit the financial statements in manufacturing companies decreased or likely to be small. Competence audit committee does not effect the relationships between audit tenure on information asymmetry. This may occur because of the existence of an audit Committee financial or accounting expertise cannot be used optimally.
Keywords: Audit Tenure, Information Asymmetry, Competence of the Audit Committee